Perception of price fairness and customer response behaviors / Nur’hidayah Che Ahmat - Che Ahmat, Nur’hidayah (2010)
Corpus of past literatures affirmed that revenue management may give a hotel a competitive edge. Howbeit, the issue of unfairness or inequality in pricing is critical within the hotel industry. Concentrating too much on profit while neglecting the customers feeling would caused organization malfunction. Hotel businesses are getting further aggressive with plethora of hotels available which honour the customer more options to choose and possess a high buying power decision. The intense rivalry among hotels drives them to be customer-oriented since customer is the king. This study empirically investigates the factors influencing perceived price fairness and the most influential one in measuring customer response behaviors. Also, this study will examine the effects of such factors on customer response behaviors. From the result, there are four factors extracted namely: 1) treatment experience, 2) price knowledge, 3) price expectation and 4) price information. Price knowledge was found to affect the customers’ reaction the most. Customers who acquire adequate knowledge about hotel room rates would not respond negatively to the hotel operators. Result has given some useful insights to the hotel operators in managing effective yield management and to be more alert on customers’ erratic behaviors